DETEKSI DINI PENYAKIT JANTUNG KORONER DENGAN PEMERIKSAAN REKAM EKG (ELEKTROKARDIOGRAM) DI RT 04 RW 01 LORONG SIANJUR, KELURAHAN 5 ILIR, KECAMATAN ILIR TIMUR II KOTA PALEMBANG - Sukma Wicaturatmashudi; Marta Pastari (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2020)
Coronary Heart Disease (CHD) or cardiovascular disease is currently one of the main and first causes of death in developed and developing countries, including Indonesia. By 2010, globally this disease will be the leading cause of death in developing countries, replacing deaths from infection. It is estimated that worldwide, CHD in 2020 will be the most common first killer, accounting for 36% of all deaths, this figure is twice as high as the death rate from cancer. In Indonesia, it is reported that CHD (which is grouped into diseases of the circulatory system) is the main and first cause of all deaths, which is 26.4%, this figure is four times higher than the death rate caused by cancer (6%). In other words, approximately one in four people who die in Indonesia is due to CHD. Various risk factors have an important role in the emergence of CHD, ranging from aspects of metabolism, hemostasis, immunology, infection, and many other interrelated factors. Coronary heart disease is a condition due to narrowing, blockage or abnormalities of the coronary arteries. Coronary heart disease is caused by narrowing or blockage of coronary arteries. This narrowing or blockage can stop blood flow to the heart muscle which is often characterized by pain (Yenrina, Krisnatuti, 1999). Coronary heart disease is heart disease due to abnormalities in the coronary vessels, namely the arteries that deliver blood to the aorta to the tissue that protects the heart cavities (Kartohoesodo, 1982). Coronary heart disease (CHD) is currently one of the main causes of death in developed and developing countries (Ministry of Health, 2006). Combined data from Clientman et al and GUSTO-I showed that the mortality rate in the first 30 days of hospitalization for patients with AMI was 52% before admission, 19% within 24 hours of hospitalization, 8% during 48 hours of hospitalization, and 21% after 30 days. . Globally, of the 55 million deaths in a year, 30% are caused by cardiovascular disease, of which almost 50% are due to AMI attacks (Yusuf, S et al 2001). (USU.ac.id)